P01.047 Improving quality of life in glioma patients: platform for exchange of patients' expertise in TTFields practice. (19th September 2018) - Kessler, A; Jentschke, E; Weiland, J; Dufner, V; Lilla, N; Linsenmann, T; Westermaier, T; Hagemann, C; Ernestus, R; Löhr, M
Abstract: Background: Glioblastoma (GBM) P: atients a: nd their R: elatives (PaR) face tremendous distress and psychological burden due to limited survival and neurological/neuropsychological deficits. Tumor Treating Fields (TTFields, alternating electric fields at 200 kHz) are a novel therapy for patients with newly diagnosed and recurrent GBM. TTFields allows PaR to actively contribute to therapy, but does require concerted attention. Additionally, PaR have to adapt to social exposure due to the visible transducer arrays. Our clinical experience shows an urgent need for personal exchange in communicating with GBM patients; especially as expressed by female patients. Establishing patient-driven support groups is limited by the rapid clinical progression of GBM. The aim of this study was to systematically evaluate the needs of PaR to implement a platform for personal interaction with focus on TTFields treatment, and to analyze the benefits experienced by PaR. Methods: Questionnaires to evaluate PaR's needs regarding meeting other PaR included: preferences for time, frequency, and maximal travel distance, type and frequency of the desired professional support. Quality-of-life and emotional function were determined two weeks before and after implementing this program by the questionnaires PHQ-2 (level of depression) and GAD-2 (level of anxiety). Additionally, perception of everyday life restriction and social exposure were analyzed by a 5-digit-scale. Results: We assessed 19 PaR using TTFields at our department. 92% expressed general interest, with 86% wanting to meet other patients, relatives (64%), their physician (73%) and psychologist (59%). Therefore, we established a meeting outside of the hospital, accompanied and supported by the treating physician and psychologist. Two weeks after the meeting, no significant changes were detected in levels of depression or anxiety in comparison to levels before the meeting. Interestingly, the meeting resulted in a strong trend towards improved perception regarding social exposure, reducing the median level from "medium" to "low" (3 points (range 2–3) before to 2 points (range 1–3) in median after the meeting, p=0.058). Similar results were obtained for perception of everyday life (p=0.182). Conclusion: This pilot trial indicates that a communication platform for TTFields patients improves the perception of social exposure and everyday life, while simultaneously meeting the assessed PaR's needs. Thus, we suggest implementing such a concept into clinical routine to improve patients' quality-of-life.